DESKRIPSI KEMAMPUAN METAKOGNISI SISWA SMA NEGERI 1 SOKARAJA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Rahmi Puspita Arum (AlphaMath : Journal of Mathematics Education, 2017)
The research aimed at describing students’ metacognitive ability in solving mathematically story question viewed from students’ learning independence in SMA Negeri 1 Sokaraja. The research was conducted in grade X-6 of SMA Negeri 1 Sokaraja on May 2016. The research method was descriptive qualitative method. The sampling technique was purposive sampling. The research subject were divided into 3 (three) groups based on the learning independence questionnaire (I.e., high, medium, and low-learning independence group). The data collection techniques used in this research were story-question test and in-depth interview. The research result showed that: (1) Students from high-learning independence group achieved strategic use level of metacognitive ability. In this level, the students were able to pass through metacognitive behavioural steps, such uas comprehending problems, selecting and using proper strategic in solving a problem, controlling problem-solving process as well as evaluating briefly. (2) students from medium level learning independence group achieved aware use level. In which they were able to comprehend a problem, but they have not been able able to control the problem solving process. (3) Students from low-level learning independence group achieved tacit use level. In this level, students solved the problem by doing trial and error since they have not be able to comprenend the problem. Therefore they were able neither to determine the proper problem solving strategy nor to solve the problem properly. Keywords: Metacognitive Ability, Learning Independence